Keanekaragaman Jenis Gastropoda (Mollusca) yang Berasosiasi dengan Ekosistem Mangrove di Taman Nasional Ujung Kulon - Nova Mujiono (Universitas Atma Jaya Yogyakarta, 2010)
A field research was conducted in Ujung Kulon National Park (TNUK) to reveal the biodiversity of Gastropoda which live associated with mangrove ecosystem. As many as 793 specimens were collected and identified. These specimen consisted of 14 families, 27 genera and 59 species which could be classified into: Native molluscs (37 species, 62.71%), Facultative molluscs (5 species, 8.47%) and Visitor mollusks (17 species, 28.81%). Within Native molluscs, 19 (51.35%) from 37 species were confirmed as new records from TNUK since they had not been recorded before. One family of Facultative molluscs, the Onchidiidae (Onchidium chameleon, O. damelli dan O. patelloides) was confirmed as new record from mangrove of Java. Totally from 59 species found here, 33 species (55.95%) were confirmed as new records, the other 26 species had already been recorded by TNUK. Some interactions (predation, mating and aggregation) among individuals were also observed in the field.